Inhibition of Cerebral High-Mobility Group Box 1 Protein Attenuates Multiple Organ Damage and Improves T Cell-Mediated Immunity in Septic Rats. (10th February 2019) - Ren, Chao; Li, Xiu-hua; Wu, Yao; Dong, Ning; Tong, Ya-lin; Yao, Yong-ming
Abstract : Sepsis remains one of the leading causes of mortality in intensive care units, but there is a shortage of effective treatments. A dysregulated host immune response and multiple organ injury are major factors for the pathogenesis and progression of sepsis, which require specific mechanism and treatment. In the present study, we performed an intracerebroventricular (ICV) injection of BoxA, a specific antagonist of high-mobility group box 1 protein (HMGB1), in septic rats that were produced by cecal ligation and puncture surgery; we further assessed the functional changes of multiple organs and splenic T lymphocytes. We found that the inhibition of cerebral HMGB1 significantly alleviated multiple organ damage under septic exposure, including damage to the heart, liver, lungs, and kidneys; reversed the immune dysfunction of T cells; and increased the survival of septic rats. These data suggest that central HMGB1 might be a potential therapeutic target for septic challenge and that inhibition of brain HMGB1 can protect against multiple organ dysfunction induced by sepsis.